2021
DOI: 10.3389/fcimb.2021.639108
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas System: A Potential Technology for the Prevention and Control of COVID-19 and Emerging Infectious Diseases

Abstract: The continued global pandemic of coronavirus disease 2019 (COVID-19) poses a serious threat to global public health and social stability and it has become a serious global public health problem. Unfortunately, existing diagnostic and therapeutic approaches for the prevention and control of COVID-19 have many shortcomings. In recent years, the emerging CRISPR/Cas technology can complement the problems of traditional methods. Biological tools based on CRISPR/Cas systems have been widely used in biomedicine. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 111 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…In recent years, emerging nucleic acid detection technologies based on CRISPR-Cas developments have opened up new opportunities for pathogen detection (Peng et al, 2020;Zhou et al, 2020;Yin et al, 2021). Compared to traditional assays, the CRISPR-Cas system has low requirements on sample quality and strong anti-interference ability and can be combined with rapid sample pretreatment technology to extract nucleic acids in the field without relying on professional equipment (Ding et al, 2021a). It has been shown that a visualized and rapid detection technology of CRISPR-Cas13a nucleic acid suitable for the lateral flow test strip technology was established by modifying biotin and small molecule antigen FAM at both ends of the reporter RNA (Gootenberg et al, 2018;Ding et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, emerging nucleic acid detection technologies based on CRISPR-Cas developments have opened up new opportunities for pathogen detection (Peng et al, 2020;Zhou et al, 2020;Yin et al, 2021). Compared to traditional assays, the CRISPR-Cas system has low requirements on sample quality and strong anti-interference ability and can be combined with rapid sample pretreatment technology to extract nucleic acids in the field without relying on professional equipment (Ding et al, 2021a). It has been shown that a visualized and rapid detection technology of CRISPR-Cas13a nucleic acid suitable for the lateral flow test strip technology was established by modifying biotin and small molecule antigen FAM at both ends of the reporter RNA (Gootenberg et al, 2018;Ding et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there are limited data regarding it as a therapeutic option for COVID-19. However, CRISPR technology has been proposed as attractive machinery for fighting against virus infection [ 132 , 133 , 134 , 135 ]. A CRISPR/Cas13 system was designed and reported, which showed a valuable tool to precisely edit the RNA [ 136 ].…”
Section: Crispr Cas Technologymentioning
confidence: 99%
“…CRISPR-based systems can control viral genomes within host cells, making them unable to transcribe and replicate [ 63 ]. Therefore, CRISPR gene editing could treat chronic infections [ 64 ]. It is particularly suited to overcoming outbreaks of viral infections because their effective control relies on effective treatment, but also on rapid diagnosis to prevent disease transmission.…”
Section: How Crispr-cas System Is Used To Diagnose and Treat Infectio...mentioning
confidence: 99%
“…Rapid detection of asymptomatic infected persons is key to controlling the epidemic, and the nucleic acid detection technology of the CRISPR-Cas system opens up a new path in mass screening. Such as SHERLOCK (Cas13a), DETECTR (Cas12a), CDetection (Cas12b) and CAS14-DETECTR in a variety of pathogen detection applications [ 64 ]. Since the outbreak of COVID-19, research on CRISPR-Cas detection of SARS-COV-2 has developed rapidly.…”
Section: Application Of Crispr-cas System In Diagnosis and Treatment ...mentioning
confidence: 99%